EFEKTIVITAS PERAN DAN FUNGSI KEPALA SEKOLAH MELAKSANAKAN PROGRAM PENINGKATAN MUTU PENDIDIKAN SD - Alben Ambarita (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aimed to analyze and describe effectivity of headmaster role and function to implementing program for improving quality of education in private elementary school of Metro City. The research approach used is qualitative with case study design on the effectiveness of headmaster role and function as educator, manager, administrator, supervisor, leader, innovator, motivator, and entrepreneur. Sources of research data are headmaster, vice headmaster, teachers, committees, supervisors, foundation, and administrative staff of schools with purposive sampling techniques. Data collection techniques used interviews, observations and documentation studies. Data analysis used Miles and Huberman interaction model is data collection, data reduction, data presentation and conclusion. The results of the study are expected to effectively implement the headmaster role and function and involve the stakeholders in an optimal manner. Keywords: effectiveness, headmaster role and function